Phenotyping Seedling Root Biometry of Two Contrasting Bread Wheat Cultivars under Nutrient Deficiency and Drought Stress - Roberta Rossi; Rocco Bochicchio; Rosanna Labella; Mariana Amato; Pasquale De Vita (Agronomy, 2024)
Roots play a key role in withstanding wheat abiotic stress. In this work, we phenotyped seedling root morphology of two semi-dwarf bread wheat cultivars, the Chinese cv Lankaodali and the Italian cv Rebelde, under the hypothesis that these two genotypes have contrasting root traits and could be used as donors in breeding programs. Root development was compared in a semi-hydroponic screening, where full-strength (FS) vs. half-strength (HS) complete Hoagland’s solution represented high and moderate nutrient availability, and a screening comparing HS solution with tap water corresponding to a condition of nutrient starvation. Genotypes were further compared in soil under full watering (100% of field capacity) vs. drought stress (50% of field capacity). Lankaodali outperformed Rebelde by producing 50% more leaf mass and 70% more root mass in FS solution, 125% more leaf mass and 106% more root mass in HS solution, and 65% more leaf mass and 36% more root mass under nutrient starvation. This cv also showed a positive correlation between leaf mass and root length and mass (between r = 0.82–0.9 and r = 0.83–0.87, respectively, p < 0.05). In the soil screening experiment, Lankaodali produced more biomass than Rebelde regardless of water availability, 48% more leaf mass, 32% more root mass, and 31% more absolute rhizosheath mass (average across water availability treatments). Lankaodali proved to be more responsive than Rebelde to both water and nutrient availability. High values of broad-sense heritability—ranging between 0.80 for root mass and 0.90 for length in a hydroponic screen and 0.85 for rhizosheath size in soil—indicate that these traits could be useful for breeding.